Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1658/1100-9233(2002)013[0585:ioacsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Invasibility of a coastal strip in NE Spain by alien plants

Abstract: The alien plant species and the ecological factors that facilitate their invasion to a coastal strip in the Baix Camp region (Tarragona, NE Spain) were studied. A detailed inventory of the area showed that 20% of the plant species, most of them from the American Continent, were aliens, many of which were strongly invasive.At the habitat level, the relationships between the invasive behaviour and a number of autecological, ecological and habitat variables were analysed by means of logistic analyses. In the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
4
25
0
5
Order By: Relevance
“…These authors reported the invasion of this tree on the South African coast. However, in the Pampean coastal region there were no clearly dominant exotic species in the sampled sites, suggesting that the stressful conditions of the studied habitats present a barrier to alien invasion (Sobrino et al 2002). These findings were in agreement with observations by Von Holle and Motzkin (2007) from coastal sand plains in the United States, who found that few invasive plants could thrive on the xeric, poor nutrient soils in the coastal region, or compete with the native species.…”
Section: Resultssupporting
confidence: 90%
“…These authors reported the invasion of this tree on the South African coast. However, in the Pampean coastal region there were no clearly dominant exotic species in the sampled sites, suggesting that the stressful conditions of the studied habitats present a barrier to alien invasion (Sobrino et al 2002). These findings were in agreement with observations by Von Holle and Motzkin (2007) from coastal sand plains in the United States, who found that few invasive plants could thrive on the xeric, poor nutrient soils in the coastal region, or compete with the native species.…”
Section: Resultssupporting
confidence: 90%
“…At the opposite end of the scale, we find the north of Africa, where tourism is not very developed and the economy is still linked to agriculture and livestock. In this case, the percentage of alien species present that have been introduced through gardening has not varied in any considerable way (Sennen and Mauricio 1934;Valdés et al 2002). It would have been desirable to have correlated the variations in time of the socio-economic factors with the presence of exotic flora.…”
Section: Discussionmentioning
confidence: 95%
“…One case where it would have been especially interesting to study the effect of socioeconomic factors is that of North Africa. Unfortunately, the catalogue of the flora of the Eastern Rif (Sennen and Mauricio 1934) was compiled at a time when there had been a colonial war between the Spanish army and the native tribes led by Abd el-Krim for more than a decade. Apart from causing the deaths of thousands of men on both sides, the war meant that it would have been impossible to carry out any accurate population census or socio-economic study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway could constitute a particularly acute threat to the colonization of sensitive rural environments. Since most release events occur adventively from inhabited areas (Sobrino et al 2002), it may also be advantageous if the escapees can survive and persist at least temporarily in urban or other ruderal habitats before successfully colonizing more widely. The requirement for such contrasting pre-adaptations may partly explain why so few species establish away from towns and cities, and the relative paucity of stresstolerators in the alien flora.…”
Section: Discussionmentioning
confidence: 99%